2013
DOI: 10.1074/jbc.m113.500967
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation of Very Low Density Lipoprotein Receptors (VLDLRs) in Neurons by Brain-derived Neurotrophic Factor (BDNF) and Reelin

Abstract: Background: VLDLR is a receptor for Reelin in brain neurons, but its mode of regulation is unclear. Results: BDNF increases VLDLR gene expression in hippocampal neurons, whereas Reelin decreases the receptor post-transcriptionally. Conclusion: Reelin down-regulates VLDLR via the E3 ubiquitin ligase Mylip/Idol. Significance: The dynamic regulation of VLDLR by BDNF and Reelin may be important for neuronal migration and brain development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…This mechanism has been shown to be regulated in a tissue- and species-dependent manner [28]. In cultured cells, it was determined that LXR activation increased IDOL transcript and protein and reduced VLDLR protein levels, implying a potential role for IDOL in development by regulating the ability of neuronal guidance cue Reelin to signal through its receptor VLDLR [27,29]. …”
Section: Lipoprotein Receptor Regulationmentioning
confidence: 99%
“…This mechanism has been shown to be regulated in a tissue- and species-dependent manner [28]. In cultured cells, it was determined that LXR activation increased IDOL transcript and protein and reduced VLDLR protein levels, implying a potential role for IDOL in development by regulating the ability of neuronal guidance cue Reelin to signal through its receptor VLDLR [27,29]. …”
Section: Lipoprotein Receptor Regulationmentioning
confidence: 99%
“…As a control for transfection efficiency, we used the Renilla luciferase pRL-TK vector (Promega). Cells were stimulated with 50 ng/ml NGF, 5 ng/ml pro-NGF, or 1 M simvastatin for 24 h followed by measurement of firefly and Renilla luciferase activities using a luminometer (Promega, Biofellows, Helsinki, Finland) as described (29,30). Results are shown as fold increase in firefly luciferase activity normalized to that of Renilla luciferase.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting-Tissue and cells were lysed in a buffer containing 150 mM NaCl, 1 mM EDTA, and 50 mM Tris-HCl, pH 7.4, supplemented with 1% Nonidet P-40, 0.25% sodium deoxycholate, 1% SDS, and protease inhibitors (24,29). Protein concentrations were determined using the Bradford assay, and an equal amount of protein per sample was subjected to SDS-PAGE and then blotted onto nitrocellulose filters (Amersham Biosciences, Helsinki, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…VLDLR downregulation may be related to the decreased number of reelin + interneurons in the dentate hilus. It is reported that BDNF increases the expression levels of VLDLR in cultured rat hippocampal neurons (Do et al ., ), suggesting that expression of Vldlr may be linked to Bdnf mRNA levels. While the reason for the decrease in reelin + interneurons by IDPN exposure is not clear, epigenetic gene silencing by hypermethylation of the promoter sequence is reported in the hippocampus of offspring after maternal deprivation in rats (Qin et al ., ).…”
Section: Discussionmentioning
confidence: 98%